Peningkatan Effisiensi Tenaga Kerja pada Lintasan Assy Wheel dengan Metode Line Balancing Ranked Positional Weight - Muhammad Ilham Akbar Hariyanto; Hery Hamdi Azwir (President University, 2021)
In the production of motorcycles at PT XYZ, there are various manufacturing processes and one of them is the Assy Wheel process. The Assy Wheel process for the K93X type performed on PT XYZ has a fairly low track efficiency. This happens because there are some unbalanced work stations where the conditions are quite detrimental to the company, so they need to be minimized or eliminated. One way to minimize unbalanced work stations is by balancing work tracks with the RPW (Ranked Positional Weight) method. This method is done by making a precedence diagram, determining the weighting of positions for each work element, sorting work elements by ranking position, placing work elements on a work station, placing the remaining time on an operation in the next sequence at the work station. After the analysis process is carried out on the Assy Wheel Track, there is a work element at the work station that needs to be changed and balanced. Work elements are combined at the next work station so that the track efficiency increases from 74% to 95%, the number of work stations and labor is reduced from four to two